2016
DOI: 10.1364/ol.41.003587
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-clad silica fibers for tailoring modal area and dispersion

Abstract: We demonstrate higher-order-mode (Aeff up to ~2000 μm2) propagation in a 100 μm outer diameter pure-silica fiber with a low-index polymer jacket commonly used for fiber-laser pump-guidance. This simple structure obviates the need for complex designs deemed necessary for realizing large-mode-area fibers. Modes ranging from HE1,12 to HE1,22 were found to propagate stably over 15 m in this fiber. The index step is approximately 4 times larger than that obtained with fluorine down doping, thus the fiber supports e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Since their discovery by Ramachandran et al 1 , Higher Order Mode (HOM) propagation of the LP0x mode in optical fibers have shown bend-resistant propagation in highly multimode (~100 micron core diameter) fibers without significant loss of modal quality. While initial experiments demonstrated near unity coupling efficiency with Long Period Gratings (LPGs) and HOM propagation in the pump cladding of dual-clad optical fibers, recent works by a variety of authors [2][3][4][5][6][7][8][9] have demonstrated coupling into standard step-index fibers utilizing both Spatial Light Modulators (SLMs) [10][11][12][13] and physical components 9,12 . Effectively, the use of an axicon phase profile generates a Bessel-Gauss beam at a specific position from the axicon.…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery by Ramachandran et al 1 , Higher Order Mode (HOM) propagation of the LP0x mode in optical fibers have shown bend-resistant propagation in highly multimode (~100 micron core diameter) fibers without significant loss of modal quality. While initial experiments demonstrated near unity coupling efficiency with Long Period Gratings (LPGs) and HOM propagation in the pump cladding of dual-clad optical fibers, recent works by a variety of authors [2][3][4][5][6][7][8][9] have demonstrated coupling into standard step-index fibers utilizing both Spatial Light Modulators (SLMs) [10][11][12][13] and physical components 9,12 . Effectively, the use of an axicon phase profile generates a Bessel-Gauss beam at a specific position from the axicon.…”
Section: Introductionmentioning
confidence: 99%